MARITIME CRYPTOLOGY - Intan Muchtadi Alamsyah (Pattimura University, 2017)
Maritime has special needs for information security, including the protection of classified information. As written in â€œCryptographyâ€™s Role in Securing the Information Societyâ€: â€˜Cryptography provides important capabilities that can help deal with the vulnerabilities of electronic information. Cryptography can help to assure the integrity of data, to authenticate the identity of specific parties, to prevent individuals from plausibly denying that they have signed something, and to preserve the confidentiality of information that may have improperly come into the possession of unauthorized parties [Dam and Lin, 1996]. Elliptic Curve Cryptography (ECC) was first introduced by Neal Koblitz and Victor Miller ([Koblitz1987],[Miller1985]). They independently introduced the elliptic curve to design a public-key cryptography. Compared to other cryptography method, it has several advantages: its arithmetic operations are spesific and can not be predicted, it offers smaller key length for the same security level compared to other method and its operations have many layers and combinations. ECC relies on the security level of the discrete logarithm problem called Elliptic Curve Discrete Logarithm Problem (ECDLP) [Hankerson et al, 2004].